Pengaruh Penggunaan Media Sosial Terhadap Kecemasan Sosial Pada Generasi Z di Kota Denpasar - Dewi, Anak Agung Ayu Meisya; Nugrahani, Rah Utami (Jurnal Pustaka Komunikasi, 2025)
This study was conducted to determine the effect of social media use on social anxiety in generation Z. According to the Central Statistics Agency (BPS), internet usage in Bali in 2022 reached 70.59% and Denpasar City became the highest area in internet usage in Bali (Including Facebook, Twitter, Youtube, Instagram, Whatsapp) reaching 84.51%. This research uses quantitative research methods. The sampling technique used in this research is non probability sampling with purposive sampling technique. The questionnaire was distributed online with the help of Google Form which was then distributed to 383 respondents who are social media users and are generation Z with an age range of 15-24 years who live in Denpasar City. The results of the data obtained were processed using SPSS version 25.0. This study uses data analysis, namely descriptive analysis, normality test, heteroscedasticity test, simple linear regression test, correlation coefficient, coefficient of determination and hypothesis testing (T test). The results showed that the use of social media has an influence on social anxiety in generation Z in Denpasar City.